2018
DOI: 10.1007/s11356-018-2769-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of three types of environmental regulation on energy consumption—evidence from China

Abstract: Based on panel data from 1997 to 2015 in China, in this paper, the direct and indirect effects of three types of environmental regulation on energy consumption are explored with the 2SLS and system GMM method. The main conclusions of this study are as follows: (1) the effects of three types of environmental regulation on energy consumption are quite varied. The cost effect of the economical environmental regulation is significant in the direct path. However, the phenomenon of "Green Paradox" emerges in legal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Regarding the influence of environmental regulations on energy consumption, a branch of studies has revealed that environmental regulations result in the cost effect and the "Green Paradox" effect [19]. The cost effect means that the production cost of polluting enterprises is increased by compliance with environmental regulation policies, thus the energy input of production decisions is accordingly adjusted.…”
Section: The Effects Of Environmental Regulationsmentioning
confidence: 99%
“…Regarding the influence of environmental regulations on energy consumption, a branch of studies has revealed that environmental regulations result in the cost effect and the "Green Paradox" effect [19]. The cost effect means that the production cost of polluting enterprises is increased by compliance with environmental regulation policies, thus the energy input of production decisions is accordingly adjusted.…”
Section: The Effects Of Environmental Regulationsmentioning
confidence: 99%
“…The policy on the IS industry is generally aimed at large and medium-sized steel enterprises, or in the eastern and central provinces and municipalities such as Beijing, Guangdong, Zhejiang, Shandong, Liaoning [55]. Therefore, environmental regulations obviously affect the CO 2 emissions in the eastern region [56]. The central and western regions are affected by geography, and there are many enterprises with small scale, low efficiency and heavy pollution.…”
Section: Heterogeneity Analysis: Sub-regionmentioning
confidence: 99%
“…At present, the methods for measuring the intensity of environmental regulations are not uniform. Some scholars measure it using a single indicator (Zhang M et al, 2019;, some scholars divide environmental regulations into different types of tools to measure separately (Yang and Song, 2019;Zhang J et al, 2021), and some scholars have measured it from the aspects of industrial solid waste composite utilization rate, industrial soot removal rate, and industrial wastewater discharge compliance rate (Liu et al, 2018). Considering that Xinjiang's…”
Section: Independent Variablementioning
confidence: 99%